Early Diagnosis and Management of Nitrogen Deficiency in Plants Utilizing Raman Spectroscopy - Huang, Chung Hao; Singh, Gajendra Pratap; Park, Su Hyun; Chua, Nam-Hai; Ram, Rajeev J.; Park, Bong Soo (Frontiers in Plant Science, 2020)
Nutrient deficiency alters growth and development of crop plants and compromises yield. Real-time non-invasive monitoring of the nutritional status of crops would allow timely applications of fertilizers to optimize for growth and yield at different times of the plant’s life cycle. Here, we used Raman spectroscopy to characterize Arabidopsis and two leafy vegetable crops under nitrogen sufficient and deficient conditions. We showed that the 1046 cm-1 Raman peak serves as a specific signature of nitrogen status in planta, which can be used for early diagnosis of nitrogen deficiency in plants before onset of any visible symptoms. Our research can be applied toward crop management for sustainable and precision agriculture.